SYNERGY OF LANGUAGE LEARNING AND VIRTUAL LEARNING PLATFORMS IN STUDIES - Buivydienė, Rūta; Mamčenko, Jelena; Piscikiene, Inga; Šustickienė, Brigita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The paper presents comprehensive study of applicability of various language learning platforms to the development of foreign language that are indicated in the Common European Framework of Reference for Language (CEFR). To carry out the research, a number of language learning platforms that are used as an alternative to Learning Management Systems (such as Moodle) was selected and on their basis a questionnaire was designed. The quantitative research involved faculty students and lecturers of Vilnius College of Technologies and design. The results of the research permitted us to draw a list of recommendations on which language learning platforms are best to be used in EFL classrooms to facilitate the development of foreign language competences.